2016
DOI: 10.1097/01.aoa.0000482617.10292.a3
|View full text |Cite
|
Sign up to set email alerts
|

Severe Secondary Postpartum Hemorrhage: A Historical Cohort

Abstract: (Birth. 2015;42(2):149–155) As postpartum hemorrhage occurring within the first 24 hours of delivery is a common cause of mortality and has been the subject of many studies, the same is not true for secondary postpartum hemorrhage, a condition in which there is significant bleeding from the genital tract anytime between 24 hours after delivery and the 42nd postpartum day. The authors of this study attempted to address this deficit in the literature by determining the incidence rate of severe secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 0 publications
3
14
0
Order By: Relevance
“…The retained products of conception (RPOC) refers to any intrauterine tissue of trophoblastic origin that is present or that develops after delivery. It was reported that 33.3% of sPPH is due to such RPOC [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retained products of conception (RPOC) refers to any intrauterine tissue of trophoblastic origin that is present or that develops after delivery. It was reported that 33.3% of sPPH is due to such RPOC [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…An arteriovenous malformation (AVM) refers to a vascular anomaly where arteries and veins are directly connected through a complex void of the usual intermediate capillary bed. AVM is reported to account for only 3.3% of sPPH [ 2 ], making sPPH due to AVM very rare, compared to RPOC. Recently, AVM has sometimes been described as ‘enhanced myometrial vascularity’ (EMV), which refers to a focus of abnormally increased vascularity in the post-partum myometrium.…”
Section: Introductionmentioning
confidence: 99%
“…While uterine atony is the predominant cause of primary PPH, retained products of conception is the leading cause of secondary PPH [2,[7][8][9] . Other causes of secondary PPH are primary subinvolution of placental bed, endometritis, pseudoanuerysm of the uterine artery, non union of uterine incision etc [10][11][12][13] . In contrast to primary PPH, the published work on the management of secondary PPH is limited [14] .…”
Section: Introductionmentioning
confidence: 99%
“…ostpartum hemorrhage (PPH) is an obstetric emergency. It is one of the top five causes of maternal mortality in both high and low per capita income countries, although the absolute risk of death from PPH is much lower in high-income countries [1] . PPH occurring in the first 24 hours after delivery may be called primary or early PPH, PPH occurring from 24 hours to 12 weeks after delivery is usually called secondary, late, or delayed PPH [1] .…”
Section: Introductionmentioning
confidence: 99%
“…It is one of the top five causes of maternal mortality in both high and low per capita income countries, although the absolute risk of death from PPH is much lower in high-income countries [1] . PPH occurring in the first 24 hours after delivery may be called primary or early PPH, PPH occurring from 24 hours to 12 weeks after delivery is usually called secondary, late, or delayed PPH [1] . PPH is formally defined as the loss of at least 500 ml of blood after a vaginal birth or the loss of at least 1,000 ml of blood after a cesarean section within 24 hours of delivery [2].…”
Section: Introductionmentioning
confidence: 99%